The Academic Goals Based on Scales of Learning, Achievement, and Social Reinforcement: A Study from Gender-Based Perceptions - Saborío-Taylor, Silvia (2023)
Several studies emphasize differences in the perception of academic goals in learning processes concerning the gender variable. This study investigates disparities in academic goals among eighth-grade students in a private school in Alajuela, Costa Rica, based on this variable. The research approach is quantitative and exploratory, following principles of the positivist paradigm. A random sample of 20 students was selected, evenly divided between males and females, aged 12 to 13 years old. A Likert-scale questionnaire called the “Academic Goals Scale” was used to collect data. The statistical analysis, using a T-Student test, did not find significant differences in academic goals based on gender. This suggests that, in this specific context, both boys and girls have similar perceptions of their academic goals in terms of learning, achievement, and social reinforcement. Although this study did not find significant differences, it highlights the importance of conducting periodic follow-up studies of a similar nature to identify potential variables that may eventually influence academic goals. This could contribute to optimizing the learning processes and gaining a deeper understanding of the factors that may influence students’ academic goals.